Effects of Poynting-Robertson (P-R) drag, radiation, and oblateness on motion around the L4, 5 equilibrium points in the CR3BP. Issue 2 (3rd July 2017) - Singh, Jagadish; Amuda, Tajudeen Oluwafemi
Abstract: The research paper under consideration investigates the motion in the vicinity of triangular equilibrium points of the circular restricted three-body problem of a passively gravitating dust particle in the gravitational field for the binaries system (Kruger 60 and Achird). The two bodies of the binary are both oblate radiating stars possessing P-R drag. The position of triangular equilibrium points of the particle is seen to be affected by oblateness, radiation and P-R drag. In our numerical exploration of the binary system Kruger 60 and Achird, we computed the radiation factors qi ( i = 1, 2) and the velocity of light cd which is a component of the P-R drag. The points are unstable due to the presence of a positive real part of the complex roots.